Establishing a computer-assisted interactive reading model - Bahari, Akbar; Zhang, Xue; Ardasheva, Yuliya (Computers and education, 2021)
Drawing on the nonlinearity and dynamicity of second language (L2) motivation and individual differences, the present study introduced and examined the computer-assisted interactive reading model (CAIRM) incorporating computer-assisted language learning (CALL) tools and affordances to assist reading comprehension in blended and distance learning contexts. The CAIRM aims at incorporating CALL tools and affordances to move L2 readers from strategic (conscious, deliberate, intentional) to automatized (reading without employing conscious strategies) processing to develop L2 reading proficiency. The model arranges emerging digital reading features to facilitate restructuring and checking content comprehension as a way to alter between bottom-up and top-down processing. To investigate CAIRM effectiveness at three levels of implementation, a between-subject design was used in a sample of 278 Iranian learners. Results indicated significant improvement on the measure of reading performance, favoring all three experimental groups (d = 2.34, d = 2.49, and d = 3.82 for bottom-up, top-down, and both processing approaches conditions, respectively). The combination of bottom-up and top-down processing strategies emerged as the most effective level of CAIRM implementation. Results also documented positive perceptions of the proposed model efficacy among participants. This suggests that offering a variety of strategies under the CAIRM—or similar models—teachers can move away from static traditional approaches based on just one particular data processing mode towards more flexible uses of the CALL tools and strategies that fit their unique teaching and their students’ unique learning styles best while supporting positive attitudes towards learning among L2 students in blended and distance learning contexts. •The study introduced the computer-assisted interactive reading model.•The model incorporates bottom-up and top-down processing strategies of L2 reading.•The effectiveness of the model was examined at three levels of implementation.•The combination of two processing strategies emerged as the most effective.•Positive perceptions of the model efficacy were documented among participants.